2021
DOI: 10.1088/1755-1315/805/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of parrotfish in Ambon Island waters, Eastern Indonesia

Abstract: Ambon is small island belongs to Maluku Province, Eastern Indonesia. The waters of this island has great potential of marine resources such as Echinoderms, Molluscs, Crustaceans, and Fishes. Coral reef ecosystem in this area make its marine waters has variety of reef fishes. One of the reef fish is parrotfish, which is important economically and ecologically. This research was conducted to study diversity of parrotfishes in Ambon Island waters. Samples were collected through UVC method and purposive sampling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Di sekeliling pulau Ambon terdapat ekosistem terumbu karang yang merupakan habitat dari berbagai jenis biota laut termasuk ikan karang. Penelitian tentang ikan karang di perairan Maluku maupun Pulau Ambon telah dilakukan oleh beberapa peneliti (Limmon et al, 2017a, b, c, d;Limmon & Pattikawa, 2017;Sahetapy dkk., 2019;Huliselan et al, 2019;Limmon et al, 2020;Loupatty et al, 2021). Walaupun penelitian ikan karang di Pulau Ambon telah banyak dilakukan, namun penelitian-penelitian tersebut lebih fokus pada keanekaragaman ikan karang baik itu berupa komposisi jenis maupun komposisi famili.…”
Section: Pendahuluanunclassified
“…Di sekeliling pulau Ambon terdapat ekosistem terumbu karang yang merupakan habitat dari berbagai jenis biota laut termasuk ikan karang. Penelitian tentang ikan karang di perairan Maluku maupun Pulau Ambon telah dilakukan oleh beberapa peneliti (Limmon et al, 2017a, b, c, d;Limmon & Pattikawa, 2017;Sahetapy dkk., 2019;Huliselan et al, 2019;Limmon et al, 2020;Loupatty et al, 2021). Walaupun penelitian ikan karang di Pulau Ambon telah banyak dilakukan, namun penelitian-penelitian tersebut lebih fokus pada keanekaragaman ikan karang baik itu berupa komposisi jenis maupun komposisi famili.…”
Section: Pendahuluanunclassified
“…Geologically, it is formed in a complex manner with high tidal wave dynamics (Salamena et al 2021) and a relatively high diversity of marine life (Limmon et al 2020) including mangroves, seagrasses, coral reefs, crabs, fishes, and mollusks (Suyadi et al 2021). Furthermore, several previous studies reported high diversity of fishes (Limmon et al 2018;Loupatty et al 2021), phytoplankton (Pello et al 2014), zooplankton (Mulyadi and Radjab 2015;Latumeten et al 2021;Huliselan et al 2021), crustaceans, cirripedia (Pitriana et al 2020;Irwansyah et al 2021), echinoderms (Setyastuti et al 2018), and gastropods (Rumahlatu and Leiwakabessy 2017;Yonow and Jensen 2018;Latupeirissa et al 2020;Wiraatmaja et al 2022).…”
Section: Introductionmentioning
confidence: 96%